Study of iron deficiency anemia with thrombocytosis in association with serum erythropoietin levels - Dr. Ramu R; Dr. Narayana Murthy C (Tropical Journal of Pathology and Microbiology, 2017)
Aim: To evaluate the correlation of iron deficiency anemia with thrombocytosis in correlation with serum erythropoietin levels. Introduction: Thrombocytosis is a common hematologic finding that can present as an incidental finding and can lead to a great diagnostic challenge. Thrombocytosis can be caused due to autonomous or as a reactive overproduction secondary to infections, iron deficiency anemia, malignancies. Erythropoietin (EPO) is the primary regulator of erythrocyte production and also affects thrombopoiesis and platelet function. The mechanism leading to thrombocytosis in cases of iron deficiency anemia (IDA) remains unclear. Hence, this study was undertaken to evaluate correlation between IDA with thrombocytosis and serum EPO levels. Materials & Methods: A total of 50 patients of all the age groups attending out-patient and inpatient departments of Basaveshwara Medical College Hospital and Research center, Chitradurga suspected of having microcytic hypochromic anemia on initial hematological investigations were included for study over a period from January 2016 to august 2016. Relevant investigations like peripheral smear study, serum iron studies and serum erythropoietin levels were subsequently performed. Results: Majority 52% (n=26) had anemia between 7-9.9 gm/dl of which 57.69% (n=15) cases had platelet count between 5-7 lakhs/cu.mm, 34.61% (n=9) cases had moderate thrombocytosis and 7.69% (n=2) cases had severe thrombocytosis. Out of 50 cases in the present study 76% (n=38) cases had significant increase in the levels of serum erythropoietin while 24% (n=12) cases had normal serum erythropoietin. Conclusion: From the present study, it may be concluded that erythropoietin would play a significant role in causing thrombocytosis in patients with iron deficiency anemia.